peningkatan mutu pendidikan Peningkatan Mutu Pendidikan di Sekolah Dasar (SD) - Nur Atikah; Yeni Resisca (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This paper aimed at determining the the quality of education in primary schools. This paper contributed to principal on improving supervision in order to have very good primary school’s performance. Since the school wishes to have good performance they should have good principal’s supervision, committee’s participation, and educators, parents of students, and the community in the school environment. Efforts to improve the quality of education that can be applied, such as; provide opportunities for teachers to improve their competencies, provide books in the library, provide training in leadership and management of school principals, renewal of infrastructure to support student comfort while in school, especially in the classroom when studying, increase community participation and the role of people parents to guide them when they are at home and in the end, namely the policies that the school makes according to the needs of the school